MEDIA AS A PARTNER OF STATE AUTHORITIES: MANAGEMENT MODELS OF INTERACTION IN THE CONTEXT OF DEMOCRATIC DEVELOPMENT - Protsenko, Valentyna (Public Management and Policy, 2025)
The article examines the interaction between mass media and state authorities as a key factor in the development of democratic institutions and effective governance in the information society. It is argued that media perform a multidimensional function: they serve as a communication channel, a social institution of public oversight, and a transformative resource for shaping public opinion and the public agenda. The theoretical part defines the concept of “state-media partnership” through three components: informational, supervisory, and collaborative, based on which a model of interaction is proposed that ensures media autonomy, pluralism of opinions, and citizen participation in shaping the public agenda. The methodological framework of the study includes an analysis of national and European legislation (the Constitution of Ukraine, Laws of Ukraine “On Information,” “On Access to Public Information,” “On Media”; the EU Charter of Fundamental Rights; European Court of Human Rights practice), a comparative analysis of international press freedom indices, and an assessment of the Ukrainian media landscape in the context of political transformation and Russia’s hybrid aggression. The empirical part identifies the following patterns: media contribute to citizen socialization, the development of political culture, and civic engagement, while their independence is often limited by economic and political dependence; structural heterogeneity and concentration of media ownership create risks of manipulation and political confrontation; the development of digital platforms increases the speed and efficiency of communication but requires enhanced journalistic professionalism and legal regulation. Based on these results, practical recommendations are proposed: ensure editorial autonomy of media, promote pluralism and social responsibility, integrate media into public governance processes through transparent and reciprocal communication mechanisms, harmonize national legislation with European standards, and develop the institutional capacity of state authorities in the field of information policy. The scientific novelty lies in integrating national legislation, international standards, and media practices into a comprehensive model of state-media partnership, which allows evaluating the quality of interaction, predicting the democratization effect of the information space, and forming management decisions aimed at increasing transparency, efficiency, and public trust.